Psychopathology Related to Energy Drinks: A Psychosis Case Report - Daniel Hernandez-Huerta; Maria Martin-Larregola; Jorge Gomez-Arnau; Javier Correas-Lauffer; Helen Dolengevich-Segal (Case Reports in Psychiatry, 2017)
Energy drinks (ED) are nonalcoholic beverages that have caffeine as their most common active substance. The rapid expansion of ED consumption has created concern in the scientific community as well as in the public opinion. We report a psychotic episode probably triggered by ED abuse in a young adult without previous psychotic disorders. We have reviewed the literature regarding the relationship between caffeine, energy drinks, and psychopathology. Few articles have been published about mental health effects of energy drinks and caffeine abuse. Nevertheless, this relationship has been suggested, specifically with anxiety disorders, manic episodes, suicide attempts, psychotic decompensation, and substance use disorder. ED consumption could represent a global public health problem because of the potential severe adverse effects in mental and physical health. To our knowledge, this article is probably the first case of psychosis related to ED abuse in an individual without previous psychotic disorders.